Value-Adding of Luxury Tourism to Enhance the Tourist Experience - Pattanapokinsakul, Kanyapat; Soonsan, Nimit; Sangthong, Suphattra (Arts of Management Journal, 2023)
Luxury tourism will continually grow in the future because it focuses primarily on providing special emotional experiences for tourists. However, luxury tourism has taken on a new meaning for the new generation of middle-class travelers, who are starting to have higher annual incomes. They usually focus on customized and cost-effective travel. Luxury tourism can be divided into health tourism, high-spending tourism, yacht tourism, and creative tourism. This group of tourists also includes senior tourists and retirement tourists because they are a group of tourists with high potential, high spending, and traveling long-term. In addition, luxury tourists like to consume brand-name and quality products that are environmentally friendly. They are willing to pay a high price for convenience and better service. To ensure success in Thailand’s luxury tourism industry, various sectors must work together and participate in promoting luxury tourism. This can be achieved through the use of technology and tourism innovations to promote luxury tourism sustainably. Ensuring consistent quality in products, services, and personnel is vital to encourage repeat tourism.